Tratamento tópico da leucoplasia pilosa bucal e desenvolvimento e validação de um instrumento para avaliação do conhecimento de cirurgiões dentistas sobre HIV/AIDS - Mariela Dutra Gontijo de Moura (2009)
This study presented was comprised of two researches. To first it was a random clinical trial to present a new topic treatment to oral hairy leukoplakia (OHL) with podophyllin resin (25%) together with penciclovir cream (1%) (PP); evaluate the predictor.s variables that could influence in podophyllin resin (25%) (P), podophyllin resin (25%) together with acyclovir cream (5%) (PA) and PP topical treatments and access the performance of these treatments,in accordance to the heal or no of OHL, rate of heal in time and recurrence twelve months after the heal of OHL. The predictor variables evaluated were: gender, age, years of formal education, route of transmission, CD4, CD8, viral load, plaques, oral candidiasis, use of highly active anti-retroviral therapy (HAART), prior use of acyclovir, prior use of antifungal, drug use by injection, use of AZT, smoking and alcohol consumption. Other study was also performed in order to identify and compare the presence or not of Epstein-Barr virus (EBV) before and after of the topical treatment of the OHL. The 42 HIV-infected patients with 69 OHL lesions were recruited randomly in the Orestes Diniz.s Treatment Center of Parasitic and Infectious Diseases, (CTR/DIP), in Belo Horizonte, Minas Gerais. The presence of the EBV was evaluated in 15 of these 42 patients, where the DNA was extracted from scrapes of the lateral border of the tongue and amplified by Polymerase Chain Reaction (PCR) before and after the topical treatment. OHL was diagnosed in accordance with exfoliative cytology. A Cox proportional hazards model was used to analyze the predictor.s variables and the performance of these treatments. The results showed that the three protocols of topical treatment presented the same hates of heal of the OHL, but after sixth week, PA protocol have a more efficiency to heal OHL comparing 13 with P and PP. Recurrence was observed in three and seven lesions treated with P and PP, respectively. Prior use of antifungal decrease the hate of heal in 59%. The 15 patients with OHL before of the topical treatment were EBV positive, but immediately after heal of the OHL, 11 patients continued EBV positive. The standard topical treatment for OHL is PA. The elevated prevalence of EBV in the lateral border of the tongue of patients without OHL after of the topical treatment supports a role of this virus in recurrence of the OHL.A study of survival analysis in a random clinical trial was performed in order to evaluate and compare the topical treatment of oral hairy leukoplakia with podophyllin resin 25% solution, podophyllin resin 25% solution in association with acyclovir 5% and podophyllin resin 25% solution in association with penciclovir 1%. For this purpose, 42 HIV-infected patients were selected, with 69 oral hairy leukoplakia treated at Orestes Diniz.s Treatment Center of Parasitic and Infectious Diseases, in Belo Horizonte/Minas Gerais. The performances analysis of these topical treatments protocols were evaluated by Cox proportional hazards model in three phases: (1) healing or no; (2) rate of heal in time and (3) recurrence twelve months after the end of treatment. The results of this study showed that the three protocols of topical treatment presented the same hates of healing of the OHL around five weeks. Podophyllin resin 25% solution in association with acyclovir 5% protocol have a more efficiency to heal OHL in a time interaction comparing with podophyllin resin 25% solution and podophyllin resin 25% solution in association with penciclovir 5%, after sixth week. For some time, the standard topical treatment for OHL is podophyllin resin 25% solution in association with acyclovir 5%.The second research carried out the development and validation of a questionnaire on dentists. knowledge of HIV/AIDS (DK-HIV-Q). The initial format of 14 the DK-HIV-Q was developed with 33 items and with four specific domains: declarative knowledge of the transmission of HIV/AIDS, declarative knowledge of oral manifestations of HIV/AIDS, procedural knowledge of proper dental practice, and procedural knowledge of infection control measures. The study was carried out in Cordoba, Argentina and because the DK-HIV-Q was developed by a Brazilian researcher, the questionnaire needed to undergo translation, cross-cultural adaptation of the items and back translation. Right away, the combined assessment of conceptual, item, semantic, operational, and measurement equivalence of the DK-HIV-Q was performed by experts. Afterwards, the DK-HIV-Q was tested in two preliminary pilot studies, with a convenience sample of 20 Argentine dentists. Subsequently, test-retest reliability was determined through the calculation of the Intraclass Correlation Coefficient (ICC) collected from 25 randomly selected Argentine dentists. Data were collected from 251 randomly selected Argentine dentists and the reliability of the instrument was assessed by Cronbach's Alpha Coefficient and the validity was assessed by exploratory factorial analysis (EFA) and confirmatory factorial analysis (CFA). The results showed that there were no significant discrepancies between the translation and the back translation. The experts completely agreed with the conceptual relevance of the instrument with 33 items. Test-retest reliability revealed the stability of the answers over a short period of time with satisfactory reproducibility of 0.95. DK-HIV-Q presented the structure with the general factor of the second order, and with four specific factors. The internal reliability was confirmed as 0.68 for the HIV/AIDS dentists. knowledge (general factor); 0.53 for declarative knowledge toward transmission of HIV/AIDS (Factor 1); 0.71 for declarative knowledge toward oral manifestations of HIV/AIDS (Factor 2); 0.59 for procedural knowledge of dentists. practice (Factor 3); and 0.48 for procedural 15 knowledge toward infection controls (Factor 4). Deletion of eight items improved the goodness of fit for the instrument and the DK-HIV-Q composed of 25 items proved to be a useful instrument for the assessment of dentists. knowledge of HIV/AIDS, and it showed that factor 2 is most closely with HIV/AIDS dentists. knowledge (general factor). Further research is required to add more items to the factors 1, 3 and 4, and to evaluate the psychometric properties with diversified samples of dentists.